2017
DOI: 10.1001/jama.2017.14972
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Therapeutic Hypothermia Initiated After 6 Hours of Age on Death or Disability Among Newborns With Hypoxic-Ischemic Encephalopathy

Abstract: IMPORTANCE Hypothermia initiated at less than 6 hours after birth reduces death or disability for infants with hypoxic-ischemic encephalopathy at 36 weeks’ or later gestation. To our knowledge, hypothermia trials have not been performed in infants presenting after 6 hours. OBJECTIVE To estimate the probability that hypothermia initiated at 6 to 24 hours after birth reduces the risk of death or disability at 18 months among infants with hypoxic-ischemic encephalopathy. DESIGN, SETTING, AND PARTICIPANTS A ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
120
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 232 publications
(137 citation statements)
references
References 47 publications
(112 reference statements)
2
120
0
6
Order By: Relevance
“…The results presented by Laptook et al. support that the findings from the two animal species of no effect of late cooling are also valid for newborn humans. In addition, an observational human cooling study showed that starting cooling between zero and three hours resulted in better motor outcome at 18 months than those who started cooling between three and six hours.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…The results presented by Laptook et al. support that the findings from the two animal species of no effect of late cooling are also valid for newborn humans. In addition, an observational human cooling study showed that starting cooling between zero and three hours resulted in better motor outcome at 18 months than those who started cooling between three and six hours.…”
supporting
confidence: 59%
“…The main conclusion from the Laptook et al. study ought to be that there is simply no real difference between the therapeutic probabilities for the two groups. In addition, with a normal prior as in Laptook et al.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…We also provided a simple example (based on Grigore et al) to familiarize them with the online tool. Finally, we included examples of Bayesian trials and analyses using informative priors . Two weeks before the elicitation workshop, we sent an evidence dossier to participants.…”
Section: Methodsmentioning
confidence: 99%
“…However, many term or near-term infants with HIE are born in non-tertiary centres without the resources or expertise to perform servo-controlled cooling and the other care modalities required by this population. The need for postnatal stabilisation and transfer to a tertiary NICU therefore precludes some infants from the benefits of optimally delivered TH and increases the risk of HIE-associated brain injury [10]. …”
Section: Introductionmentioning
confidence: 99%